Caracterização e atividade antifúngica in vitro do poli (metil metacrilato) modificado pelo cinamaldeído - Sousa, Taisa Mara dos Santos (2018)
In order to be useful in users of acrylic-based orthodontic appliances, the antifungal activity and characterization of cinnamaldehyde (CIN) modified poly (methylmethacrylate), (PMMA), was analyzed in vitro. Initially, minimal inhibitory concentrations (CIM) and Fungicide (CFM) of cinnamaldehyde on strains of Candida albicans ATCC 60193, C. krusei ATCC 34135, C. glabrata ATCC 2001 and C. tropicalis CBS 94, and their effect on the multispecies fungal biofilm. After incorporation of the phytoconstituent into PMMA, the antifungal effect was evaluated by diffusion into agar and inhibition of fungal adherence. For the PMMA / CIN system were a surface roughness; microhardness; «Calorific by thermogravimetry (TG) and differential scanning calorimetry (DSC); incorporation of the CIN by Fourier transform infrared spectroscopy (FTIR) and its controlled release by visible ultraviolet (UV / VIS) spectroscopy. Data were analyzed from descriptive and inferential statistics (p = 0.05). A CIM and CFM made an adjustment with the same value of 125 μg / mL, promoting the inhibition of Candida multispecies biofilm (p <0.05). PMMA modified by the addition of 24% CIN was antifungal to 28 mm inhibition halos, and is applied to the surface of the biofilm on the surface of the modified PMMA. PMMA unmodified (control) or containing 12 and 24% minimum CIN less than 0.23; 0.27 and 0.35 μm for 24% CIN (p <0.05), and Sz of 1.72; 2.24; 2.28 for all groups (p <0.05). A Vickers microhardness with the initial average of 13.87; 13.52; 10.82 and mean, after 90 days, of 15.89; 14.88 and 13.46, respectively, for PMMA without and with 12 and 24% CIN. The presence of CIN in PMMA was confirmed by DSC, TG, FTIR and UV / VIS. PMMA containing 24% CIN had a strong antifungal potential and was considered a promising therapeutic method in the prevention of candidiasis.